ANALISIS KONDISI FISIK PADA ATLET DI AKADEMI FUTSAL SEMARAPURA TAHUN 2024 - Arijaya, Kadek Sukma; Hidayat, Syarif; Eka Budi Darmawan, Gede (Universitas Tunas Pembangunan, 2025)
Physical condition is very much needed in every athlete's achievement improvement. This is the basis that must be considered to achieve maximum achievement. This study aims to determine the level of physical condition of athletes at the Semarapura Futsal Academy located at Jalan Kenyeri V, Klungkung Regency, Bali. The type of this research is quantitative descriptive research. The subjects of this study were all athletes at the Semarapura Futsal Academy totaling 30 people, with an age range of 13-19 years. Data collection carried out in this study was by survey method, namely with test and measurement techniques. Data analysis used descriptive statistical analysis techniques which were presented in the form of percentages in tables and graphs. The research instrument used was the physical condition test of the Semarapura Futsal Academy Athletes, namely 1) leg muscle strength test (leg dynamometer), 2) cardiovascular endurance test (Multistage Fitness Test / MFT), 3) agility test (shuttle run), 4) flexibility test (sit and reach), and 5) balance test. The results of this study indicate that the physical condition profile of athletes at the Semarapura Futsal Academy in 2024 is mostly in the